Between politicians and masters of popular culture: discourse, power and ideology in museums (Cadernos de Sociomuseologia, 2014)
The narratives produced in expográficos circuits discourses are loaded with meanings, intentions and ideologies that can be analyzed from the exposed objects, the voids, the said and the unsaid. From a theoretical contribution of authors related to the social sciences and, specifically, to the field of Sociomuseology working with the issue of construction of discourses, memory and power, this article aims to analyze the discourses of expográficas narratives of a traditional museum, Municipal Museum of Borborema, and a community museum, the Museum of the Living Eye School Time, both located in the State of Paraíba. In this perspective, the analysis goes through about social subjects are represented in these two museums, diametrically opposed in the form of construction of its exhibitions.Keywords: museums, speech, memory, power, ideology